Use of mulberry foliage for pigs in the integrated tropical systems - Ly, Julio; Samkol, Pok (Cuban Journal of Agricultural Science, 2014)
An intense work of research was carried out in different areas of the tropics between 1993 and 2003. The investigation was about the use of shrub-like and arboreous foliage of mulberry (Morus alba) as a source of protein for feeding pigs. The mulberry can be used in the tropic as a permanent crop integrated to systems of animal production, mainly of swines. According to the existing information about the use of mulberry foliage for feeding growing/fattening pigs, the conclusion was that between 20 and 25 % of the total ration could be constituted by mulberry foliage. The age of cut and the management of the planting fertilization are among the factors that can influence on the response of the herd. Further researches should be required but, over all things, the implementation of the available results for increasing the efficiency of the systems of swine production through the integration of the tree component as an essential subsystem because there are already enough data that benefit the use of mulberry foliage for feeding pigs. Key words: pigs, mulberry, Morus alba, integrates systems, tropics